TRANSLATION STRATEGIES ADOPTED BY ENGLISH DEPARTMENT STUDENTS IN COPING WITH NON EQUIVALENCE PROBLEMS - Esti Junining (Universitas Brawijaya, 2014)
Translation skill is undoubtedly needed by university students to uncover the problems in understanding textbooks written in English. Despite the need, there are still few students using appropriate strategies to help them comprehend the textbooks. This is due to their lack of understanding in the theories of translation which more or less help them translate the textbooks well. This paper is intended to find out appropriate strategies adopted by English department students in coping with problems with non equivalence. Sixty five English department students have participated in this small survey. The data were collected by asking the students to translate three different genres of texts, from informational text, literary text and news. From the translation process, the students will face problems with non equivalence from each different genre of a text. This small survey revealed the common translation strategies adopted by the English department students in translating informational text, literary text and news. The underlying finding will reveal the typical strategies used to deal with the problems of non equivalence in informational text, literary text and news. At the end of the paper, it is suggested that the students undergo more practice in translation using the seven strategies of translation.